Vitamin D inhibits TNF-α serum level in wistar rats stimulated with Porphyromonas gingivalis - Hervina, Hervina; Syahriel, Dwis; Wedagama, Dewa Made; Nurlitasari, Dewi Farida; Nasutianto, Haris; Haryani, I Gusti Ayu Dewi (Majalah Kedokteran Gigi Indonesia, 2023)
Periodontitis is a chronic inflammation of the periodontal tissues initiated by increased proinflammatory cytokines such as TNF-α due to the induction of Porphyromonas gingivalis (Pg). This study aimed to analyze the effect of vitamin D (cholecalciferol) on TNF-α serum level in Wistar rats stimulated with Pg to induce periodontitis. Twenty-seven male Wistar rats (n = 27) were divided into three equal groups. Group I was healthy Wistar rats that received 2000 IU vitamin D once a day. Group II was Wistar rats stimulated with Pg and received 2000 IU vitamin D, while group III was Wistar rats stimulated with Pg but did not receive vitamin D. Blood was collected through the orbital sinus and centrifuged to get the serum. TNF-α serum levels were assessed using Elisa method on the 7th, 14th, and 28th. The data were normally distributed and homogeneous. The mean TNF-α data was analyzed for differences between groups using the one-way ANOVA and LSD post hoc test. Significant differences were seen in group II (418.49 ± 161.08 ng/mL) and group III (172.16 ± 104.18 ng/mL) on the 28th day (p = 0.001). The findings suggest that vitamin D inhibits the TNF-α serum level in Wistar rats stimulated with Pg on the 28th day.